(543) السيبرنتيكا وعلم الاقتصاد Cybernetics and Economics - ترجمة أحمد هاشم مراجعة د. محمد رضا العدل (معهد التخطيط القومي, 2026)
يُقدم هذا الملف، ترجمة لمقالة علمية حول "السيبرنتيكا وعلم الاقتصاد". يتناول الملف مفهوم السيبرنتيكا كعلم للتحكم والتوجيه، ويقارن بين إمكانيات استخدامه في النظامين الرأسمالي والاشتراكي، مؤكداً أن التخطيط الشامل في الاقتصاد الاشتراكي يوفر البيئة المثلى لتطبيق الأساليب السيبرنتيكية. ويركز الملف بشكل أساسي على دور الحواسيب الإلكترونية في تحويل العمليات الحسابية اليدوية البطيئة إلى أنظمة آلية سريعة ودقيقة، مما يتيح لصناع القرار الحصول على معلومات فورية وشاملة عن حالة الاقتصاد القومي وتدفق البيانات بين مختلف قطاعاته.كما يستعرض الملف المجالات الحيوية لتطبيق السيبرنتيكا في الاتحاد السوفيتي آنذاك، ومن أبرزها تطوير نظام المتابعة والإحصاء لبناء موازين "المدخلات والمخرجات" التي توضح العلاقات التشابكية بين القطاعات الإنتاجية. ويوضح الملف كيف تساهم هذه الأساليب في تحسين عمليات التخطيط طويل الأمد وتحديد الاحتياجات الفعلية من الموارد والطاقة، وصولاً إلى ضبط نظام الأسعار والأجور بشكل علمي يعكس التكاليف الحقيقية للإنتاج. وبذلك، يبرز الملف السيبرنتيكا كأداة استراتيجية لرفع كفاءة الإدارة الاقتصادية وتحقيق "أمثلية الخطة" عبر إنتاج أقصى كمية من المنتجات بأقل قدر من الاستهلاك للموارد والقوى العاملة. This document presents a translation of a scholarly article on "Cybernetics and Economics." It explores the concept of cybernetics as a science of control and direction, comparing its potential applications in capitalist and socialist systems. The article emphasizes that comprehensive planning in a socialist economy provides the optimal environment for implementing cybernetic methods. It focuses primarily on the role of computers in transforming slow, manual calculations into fast and accurate automated systems, enabling decision-makers to obtain immediate and comprehensive information about the state of the national economy and the flow of data between its various sectors. The document also examines the vital areas of cybernetics application in the Soviet Union at the time, most notably the development of a monitoring and statistical system for constructing "input-output" balances that illustrate the interrelationships between production sectors. It explains how these methods contribute to improving long-term planning processes and determining actual resource and energy needs, ultimately leading to the scientific adjustment of prices and wages to reflect the true costs of production. Thus, the document highlights cybernetics as a strategic tool for enhancing the efficiency of economic management and achieving "plan optimization" by producing the maximum quantity of goods with the least consumption of resources and labor.